Present tendencies of annual cycle rainfall change in Ukraine - Zatula, Vasyl (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Introduction. The precipitation regime, its amount and distribution throughout the year are an important component of the climate characteristics. This information is of exceptional importance in the planning and management of water resources.The purpose of article is to present an expanded description of the annual cycle of atmospheric precipitation in Ukraine and to identify the most important features of its change over the period 1961-2020.Data and methods. This paper examines the features of the annual cycle of atmospheric precipitation in the continental part of Ukraine. The research is based on data from climatological reference books at 153 weather stations across the country. Much attention is paid to the parameters of the harmonic analysis of the initial observation series in 1961-1990 and 1991-2020 and the residual series formed on their basis with changes in precipitation, primarily the amplitude  and the phase  of the annual harmonic, as well as its contribution  to the total variance of monthly precipitation series.Results. Changes in the repeatability of gradations of the amplitude of the annual harmonic of atmospheric precipitation are analyzed. A comparison of the statistics of the series of the annual harmonic amplitude  and annual amplitude  of atmospheric precipitation at weather stations of Ukraine during 1961-1990 and 1991-2020 is carried out. Changes in the statistical distributions of the repeatability of gradations of annual and semi-annual harmonics by their contribution to the total variance of rainfall annual cycle in Ukraine in different observation periods were considered. The repeatability of gradations of the timing of annual harmonic of atmospheric precipitation maxima in these periods is analyzed. Significant spatial heterogeneities in the distribution of annual and monthly precipitation amounts were found. Harmonic analysis also allowed us to identify important patterns within the annual cycle. The main role in seasonal fluctuations in monthly precipitation amounts is played by the annual, and less often - semi-annual harmonics. During the transition from the first observation period (1961-1990) to the second (1991-2020), the inverse relationship between the parts of the variance caused by these harmonics noticeably weakened (the coefficient of determination  between the parameters  and  of the annual and semi-annual harmonics decreased from 0.876 to 0.661). At the same time, the slope of the linear relationships between these parameters significantly decreased (the coefficient of the linear regression equation changed from -0.771 to -0.47).The scientific novelty. It has been established that the amplitude and phase structure of the annual harmonic, as well as the relative role of the annual and semi-annual harmonics of monthly precipitation in the current climate, have undergone significant changes. This is probably due to changes in the nature of atmospheric circulation over the entire Atlantic-European sector, although the influence of local climate-forming factors cannot be completely excluded either.Practical significance. The identified changes in the phase structure and other characteristics of the annual harmonics of monthly precipitation series contribute to a better understanding of current trends in the evolution of the regional climate system in Ukraine and will be useful for long-term climate change forecasting.